Role of The Private Sector in Managing the Country's Economy and Territory - Dina Ayu Lestari; Eli Apud Saepudin; Firatna Amandari; Asqi Savira Anaya; Angeliana Artamevia Salsabila (UNIVERSITAS SERAMBI MEKKAH, 2024)
Limited APBN and APBD funds owned by the government, as well as the country's territory which still requires several roles of the private sector and the state to balance the various problems that occur in a particular area. that the role of the government and the private sector are seen as very important in supporting the economy. In addition, the center of center of economic development is the development of infrastructure that with guaranteed economic development and maintenance of the country's territory in accordance with what is needed, the role of the private sector and the state is very necessary to lead to a developed country.